Knowledge, attitude and practice on hepatitis B prevention among dental professionals in India - R. Sudhakara Reddy; L. A. Swapna; T. Ramesh (Universidade Estadual de Campinas, 2015)
Aim: To obtain comprehensive information about the knowledge, attitude and practices towards hepatitis B infection by dental health care professionals, and their effort to prevent the transmission among the patients. Methods: A cross sectional survey conducted among 540 dental health care workers in a dental college and private practitioners in and around Bhimavarm, India. A selfassessment questionnaire with queries on levels, namely knowledge and practices, and protective measures to prevent transmission of hepatitis B was recorded and statistically analyzed. Results: Frequency distribution scores of knowledge, attitude and practice in relation to hepatitis B infection revealed that the faculty members, the students under training along with, nurses, hygienists and lab technicians were relatively aware of hepatitis B vaccination, precautions and principles droplet isolation procedures to prevent transmission of hepatitis B infection. Conclusions: The results showed that the dental professionals had good knowledge and attitude regarding hepatitis B and its transmission, but that the infection control measures among the health care professionals are moderately poor and an educational program on isolation precautions can further enhance these levels and thereby, reducing the risk of infection transmission .